Kawamoto’s "Dojoji Temple": Puppetry, Gesture and Myth - Lina, Nurul; Naeim, Fauzi (Arte, Individuo y Sociedad, 2015)
Dojoji Temple ( Dōjōji, 1976) is a short puppet animation directed by Kihachirō Kawamoto. Influenced by Bunraku (Japanese puppet plays), emaki (painted scroll), Noh theatre and Japanese myth, Dojoji Temple tells of a woman’s unrequited love for a young priest. Heartbroken, she then transforms into a sea serpent and goes after the priest for revenge. While Kawamoto’s animation is rich with Japanese aesthetics and tragedy, his animation is peopled by puppets who do not speak. Limited and restrained though the puppets may be, their animated gestures speak volumes of powerful emotions. For our article, we will select several scenes from the animation, and interpret their actions so that we can further understand the mythical world of Dojoji Temple and the essential being of puppetry. Our gesture analysis will take into account cinematographic compositions, sound and bodily attires, among other elements.